Secukinumab Demonstrates Sustained Efficacy and Safety in a Taiwanese Subpopulation With Active Ankylosing Spondylitis: Four-Year Results From a Phase 3 Study, MEASURE 1 - Tseng, Jui-Cheng; Wei, James Cheng-Chung; Deodhar, Atul; Martin, Ruvie; Porter, Brian; McCreddin, Suzanne; Talloczy, Zsolt (Frontiers in Immunology, 2020)
Objectives: To present the long-term (4-year) efficacy and safety of secukinumab in Taiwanese patients with active AS in the MEASURE 1 extension study. Methods: This post hoc analysis reports data from Taiwanese patients originally randomized to subcutaneous secukinumab 150 or 75mg or placebo every 4 weeks (following intravenous loading dose) who were invited to enter the 3-year extension study. Assessments at Week 208 included ASAS20/40 responses and other clinically relevant endpoints. Efficacy data are presented as observed. Safety analyses included all patients who received ≥1 dose of secukinumab. Results: Of the 57 Taiwanese patients in the core trial, 48 entered the extension study and 87.5% patients (42/48) completed 4 years of treatment. Thirteen Taiwanese patients (including placebo-switchers) were escalated from 75 to 150mg (approved dose) at some point starting from Week 172. ASAS20/40 responses were sustained through 4 years in the Taiwanese patients who were originally randomized to secukinumab 150mg. Clinical responses were improved in those patients who received dose-escalation from 75 to 150mg during the study. No unexpected safety signals were reported. Conclusion: Secukinumab 150mg demonstrated sustained efficacy over 4 years in Taiwanese patients with active ankylosing spondylitis. The safety profile of secukinumab was consistent with previous reports.